Synthesis of graphene oxide: A refined approach - Maria Refalo Magro; Daniel A. Vella; Glenn Cassar (Carbon Trends)
The conventional method for preparing graphene oxide (GO) relies on the use of corrosive acids namely concentrated H2SO4, HNO3, and H3PO4 as well as aggressive oxidizing agents such as KMnO4 and KClO4. The application of heat further exacerbates the preparation, promoting the release of harmful acidic NOx and ClO2 fumes. The formation of the by-product Mn2O7 could also increase the risk of explosion. A safe(r) and shorter method of preparation of GO has been a challenge for many researchers. This study presents a method of preparing GO, that reduces risks by eliminating the need for heating and shortening the oxidation step. This method utilises mixtures of concentrated H2SO4 and KMnO4 with graphite thus eliminating the release of toxic fumes.Characterization studies revealed that the graphite precursor with an average lateral flake size of 15.06 ±1.87 µm was successfully oxidized to GO and subsequently exfoliated to thinner sheets. The resulting GO exhibited a reduced average lateral sheet size of 10.22 0.62 µm and comprised approximately 10 layers, indicating that the precursor material is polycrystalline. Comprehensive XPS analysis revealed that the oxygen content and chemical states of carbon in the synthesized GO was comparable to that of commercially available GO, with similar distribution of oxygen functionalities. In the in-house produced GO, the predominant functional group was found to be the C-O bond corresponding to the epoxy group, followed by the ester and acid anhydride functional groups. Furthermore, the decrease in the percentage of sp2 hybridized carbon in GO to 45.52 %—measured using X-ray induced Auger spectroscopy—confirms the successful oxidation of the precursor, which initially exhibited 80.21 % sp2 character in graphite.